Comparison of Treatment Duration for Drug-Sensitive Tuberculosis in Patients With and Without HIV Infection - Muhammad Fachri; Farrah Salsabilla Ardhia; Raden Mirsyam Ratri Wiratmoko; Faisal Irsyad Ardhia (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2026)
Background: Indonesia had 842,000 new TB cases and 116,400 TB deaths in 2018, including TB-HIV cases. TB-HIV co-infection remains a major health concern. Objective: To compare the duration of treatment of drug-sensitive tuberculosis in patients with and without HIV at Jakarta Cempaka Putih Islamic Hospital, Jakarta Sukapura Islamic Hospital, and Jakarta Pondok Kopi Islamic Hospital for the period September 2022 to September 2024. Methods: A cross-sectional study with a total sampling technique was conducted on 82 patients. The analysis used an independent T-test to compare treatment duration. Results: Of the 105 patients, 15 had drug-sensitive tuberculosis with HIV and 90 without HIV. The majority of patients were men (66 samples), with the largest age group being 35-44 years old. No significant difference in treatment duration was found between drug-sensitive tuberculosis patients with and without HIV (p= 0.569). Conclusions: Comparison of the duration of treatment for drug-sensitive TB patients with and without HIV was the same, and there was no significant difference.